PRINCIPALS’ ADMINISTRATIVE COMPETENCIES IN THE MANAGEMENT OF SCHOOL PLANT IN PUBLIC SECONDARY SCHOOLS IN IKOM EDUCATION ZONE OF CROSS RIVER STATE - Ekpung, Akata, Charles; Effiong, Anietie Imo (ANTIS PUBLISHER, 2025)
Objective: This study focused on Principals’ Administrative Competencies in the management of School Plant in Public Secondary Schools in Ikom Education Zone of Cross River State. Method: The design of this study was descriptive survey research design aimed at eliciting information from the respondents based on the research questions and null hypotheses that guided the conduct of this study. The population of the study comprised 113 principals and 1487 teachers of public secondary schools in Ikom Education Zone of Cross River State while sample of the study comprised of 200 teachers and 38 principals using a multi stage sampling technique. The instrument used for data collection was structured questionnaire and data were analyzed using mean and standard deviation for research question and t-test was used to test the null hypotheses at 0.05 level of significance. Results: The findings of the study revealed that procurement-related competencies and utilization-related competencies are needed by secondary school principals while the findings in the hypotheses revealed that there is no significant difference in the mean rating of principals and teachers on the procurement-related competencies needed by principals in school plant management; there is no significant difference in the mean rating of principals and teachers on the utilization-related competencies needed by principals in school plant management. Novelty: Based on the findings, the study revealed that secondary school principals should be subjected to in-service training on the usage of school plants for effective management.